2014
DOI: 10.1259/bjr.20130263
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of benign from malignant thyroid nodules with acoustic radiation force impulse technique

Abstract: Objective: The aim of our study was to assess the performance of acoustic radiation force impulse (ARFI) imaging to differentiate benign from malignant thyroid nodules. Methods: 182 patients who needed thyroid surgery were examined. All patients and 50 healthy volunteers underwent ARFI sonoelastography, which quantitatively analysed the elasticity and hardness of the nodule's centre and periphery.Results: ARFI values showed a statistical significance between malignant nodules and benign nodules and common thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 16 publications
1
19
1
1
Order By: Relevance
“…The reason for this results is that our study included 20 published articles about SWE, while there only 5 included studies in the article of Zhang et al [13] and 15 in the article of Lin et al [86]. Then, contrasting with these included studies, our study not only contained the case control studies which have high sensitivity and specificity, like Zhuo et al [78] and Sebag et al [10] (SEN = 0.963, SPE = 0.962; SEN = 0.852, SPE = 0.939), but also incorporated those with poor results, like Xu et al [73] and Szczepanek-Parulska et al [63] (SEN = 0.682, SPE = 0.769; SEN = 0.761, SPE = 0.641). Hence, SWE have a slight lower, but a more robust result based on our abundant included studies.…”
Section: Discussionmentioning
confidence: 95%
“…The reason for this results is that our study included 20 published articles about SWE, while there only 5 included studies in the article of Zhang et al [13] and 15 in the article of Lin et al [86]. Then, contrasting with these included studies, our study not only contained the case control studies which have high sensitivity and specificity, like Zhuo et al [78] and Sebag et al [10] (SEN = 0.963, SPE = 0.962; SEN = 0.852, SPE = 0.939), but also incorporated those with poor results, like Xu et al [73] and Szczepanek-Parulska et al [63] (SEN = 0.682, SPE = 0.769; SEN = 0.761, SPE = 0.641). Hence, SWE have a slight lower, but a more robust result based on our abundant included studies.…”
Section: Discussionmentioning
confidence: 95%
“…All the quality assessment items of the included studies had a low risk of bias except for one study [38] did not describe the reason for the excluded patients.…”
Section: Methodology Quality Assessmentmentioning
confidence: 99%
“…Six papers were further excluded because the authors analyzed the SWE but not SWV. Therefore, 13 studies [26][27][28][29][30][31][32][33][34][35][36][37][38] were ultimately included in the meta-analysis. Figure 1 lists the diagram of the study selection process.…”
Section: Literature Searchesmentioning
confidence: 99%
“…(v) Only original complete publications (no editorials letters, abstracts or reviews) were included in the analysis, and complete reported data (sensitivity, specificity) were necessary to calculate the true positive (TP), false positive (FP), false negative (FN) and true negative (TN) cases. The studies were excluded for one of three reasons (i) In the presence of incomplete data (n 5 2) Zhuo et al 2014), the corresponding author was contacted and required to provide the missing data via E-mail; the study would be excluded if the author did not reply. (ii) Diffuse thyroid diseases other than thyroid nodules were included in the study (n 5 1) (Sporea et al 2012).…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%